IMPLEMENTATION OF LEARNING BY GAMES METHOD TO IMPROVE SELF-HELP SKILLS IN WASHING STUDENTS WITH DISABILITIES - Latifatul Faizah; Muhammad Munif (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Students with intellectual disabilities have intellectual limitations that affect their ability to understand concepts, including self-cultivation skills such as purification (thaharah). Thaharah is an important part student of religious education that needs to be taught to support students' independence in everyday life. However, conventional learning is often less effective in delivering fiqh material to students with intellectual disabilities because of its abstract and difficult to understand nature. Therefore, appropriate, fun, and innovative learning methods are needed. The Learning by Games method was chosen as an approach that can increase student engagement, help them understand the material more concretely, and create a pleasant learning atmosphere. The purpose of this study was to explore the implementation of this method in improving self-cultivation skills in students with intellectual disabilities. The study was conducted with a qualitative approach using a multi-site case study design at SLBN Demung Besuki and SLB Dharma Wanita Situbondo. Data collection techniques included observation, interviews, and documentation, and were analyzed using the Miles and Huberman model (data reduction, data presentation, and verification). The results of the study showed that the Learning by Games method, through various types of games such as video games, puzzles, board games, roles, and footprints, was able to improve understanding and practice of independent purification. This method also has a positive impact on student interaction, attention, and skill development in learning